Recent advances in understanding spleen tyrosine kinase (SYK) in human biology and disease, with a focus on fostamatinib. (1st January 2023) - Cooper, Nichola; Ghanima, Waleed; Hill, Quentin A; Nicolson, Phillip LR; Markovtsov, Vadim; Kessler, Craig
Abstract: Spleen tyrosine kinase (SYK) is an important regulatory molecule of signal transduction pathways involved in the pathogenesis of autoimmune diseases such as immune thrombocytopenia (ITP), and the SYK-signaling pathway has emerged as a potential target for the treatment of numerous diseases. The aim of this narrative review is to summarize the biological properties of SYK and its involvement in disease pathways, provide an update on SYK inhibitors in the treatment of ITP, and consider other potential applications. Fostamatinib, the only licensed SYK inhibitor to date, produces clinical response in ITP patients, including those who are refractory to other treatments. It appears to reduce the risk of thrombotic events and may therefore be a drug to consider for patients with an increased thrombotic risk. Encouraging results have also been obtained in the treatment of warm autoimmune hemolytic anemia. Several other SYK inhibitors have entered clinical trials for a range of indications, reflecting the ability of these drugs to affect multiple signaling pathways. SYK inhibitors have the potential to target several aspects of COVID-19 pathogenesis including thrombosis, without affecting normal hemostasis, and data from the first study of fostamatinib in COVID-19 are encouraging. It is hoped that ongoing trials in autoimmune indications other than ITP, as well as in hematological malignancies and other disorders, confirm the promise of SYK inhibitors. Plain Language Summary: Immune thrombocytopenia (ITP) is an autoimmune disease that usually happens when your immune system mistakenly attacks and destroys platelets, which are cells that help blood to clot. Individuals with ITP can experience easy or excessive bruising and bleeding. Scientists have identified that an enzyme called spleen tyrosine kinase (SYK) is involved in numerous biological processes that are associated with the immune system response, inflammation, and some types of cancer in humans. Therefore, it has become a target for new drugs which inhibit the action of SYK. In this review article, the authors provide a summary of the biological properties and actions of SYK and its involvement in various diseases, discuss information about drugs that have been developed as SYK inhibitors for the treatment of ITP, and consider other potential uses for drugs that inhibit SYK. Although several drugs are being developed, the only SYK inhibitor that is currently available for the treatment of ITP is a drug called fostamatinib. In patients with ITP, including those who no longer respond to other treatments, fostamatinib has been shown to improve platelet counts and reduce bleeding events. Researchers are also currently investigating the use of drugs that inhibit SYK, including fostamatinib, for the potential treatment of other diseases associated with inflammation (e.g. rheumatoid arthritis, COVID-19), autoimmunity (e.g. warm autoimmune hemolytic anemia), and blood cancers (e.g. lymphoma, chronic lymphocytic leukemia, and acute myeloid leukemia).